The Acquisition of the scr Gene Cluster Encoding Sucrose Metabolization Enzymes Enables Strains of Vibrio parahaemolyticus and Vibrio vulnificus to Utilize Sucrose as Carbon Source - Hammerl, Jens Andre; Göllner, Cornelia; Jäckel, Claudia; Swidan, Fatima; Gutmann, Helena; Strauch, Eckhard (Frontiers in Microbiology, 2021)
Most strains of Vibrio parahaemolyticus are unable to utilize sucrose as carbon source, though few exceptions exist. We investigated a sucrose-positive V. parahaemolyticus strain by whole-genome sequencing (WGS) and confirmed the presences of a genomic island containing sucrose utilization genes. A 4.7 kb DNA cluster consisting of three genes: scrA encoding a sucrose uptake protein, scrK encoding a fructokinase, and scrB coding for a sucrose-6-phosphate hydrolase, was PCR amplified and inserted into the Vibrio/E. coli shuttle vector pVv3. Two recombinant plasmids, only differing in the orientation of the insert with respect to the pVv3-lacZα-fragment, conferred the E. coli K12 transformants the ability to utilize sucrose. The introduction of the two plasmids into sucrose-negative V. parahaemolyticus and V. vulnificus strains also results in a change of the sucrose utilization phenotype from negative to positive. By performing a multiplex PCR targeting scrA, scrK, and scrB, 45 scr-positive V. parahaemolyticus isolates from our collection of retail strains were detected and confirmed to be able to use sucrose as carbon source. Strains unable to utilize the disaccharide were negative by PCR for the scr genes. For in-depth characterization, 17 sucrose-positive V. parahaemolyticus were subjected to WGS. A genomic island with a nucleotide identity of >95% containing scrA, scrB, scrK and three additional coding sequences (CDS) were identified in all strains. The additional genes were predicted as a gene coding for a transcriptional regulator (scrR), a porin encoding gene and a CDS of unknown function. Sequence comparison indicated that the genomic island was located in the same region of the chromosome II in all analyzed V. parahaemolyticus strains. Structural comparison of the genomes with sequences of the sucrose utilizing species V. alginolyticus revealed the same genomic island, which indicates a possible distribution of this genetic structure by horizontal gene transfer. The comparison of all genome sequences based on SNP differences reveals that the presence of sucrose utilizing genes is found in genetically diverse strains and is not restricted to a subset of closely related strains.